Quantity Rationing and Concavity in a Flexible Household Labor Supply Model - Kapteyn, Arie; Kooreman, Peter; van Soest, Arthur (The Review of Economics and Statistics, 1990)
Arie Kapteyn, Peter Kooreman, Arthur van Soest, Quantity Rationing and Concavity in a Flexible Household Labor Supply Model, The Review of Economics and Statistics, Vol. 72, No. 1 (Feb., 1990), pp. 55-62